Diazinon mediated biochemical changes in the African toad (Bufo regularis) - Isioma Tongo; Lawrence Ezemonye; Uche Ochei (MDPI AG, 2012)
The sublethal toxicity of diazinon to the adult African toad, Bufo regularis was assessed using an integration of biomarkers. Changes in acetylcholinesterase (AChE), corticosterone and total protein levels were assessed in the serum, brain, liver, lungs and gastrointestinal tract (GIT) and the results supported by bioaccumulation data. The biomarkers were chosen as indicators of key physiological functions: AChE for neurotoxicity, corticosterone and total protein levels as indicators of oxidative stress. Toads were exposed to 0.01, 0.02, 0.03 and 0.04 g/L for 28 days. Brain AChE activity reduced by 96% in the highest concentration (0.04 g/L) compared to the control brain. Similarly, AChE activities in serum, liver, lungs and GIT tissues (88%, 88%, 87, 87% umg-1 protein respectively) were also inhibited in the toads. Corticosterone and total protein levels in the tissues decreased compared to the control. The accumulation results obtained showed accumulation in the tissues (liver>serum>brain> lung>GIT), with a direct relationship between tissue concentration and changes in the biochemical indices. The alterations in all the indices were significantly concentration dependent. The biomarkers described in this study could be useful complementary indices in the risk assessment of diazinon pesticide.